Extraabdominal desmoid tumor of post-traumatic origin. - Croci, Fabio; Caballero, Ricardo; Rocca, Guillermo; Mariño, Ana (Cirugía del Uruguay, 1988)
A case of extraabdominal desmoid tumor of early post-traumatic origin, located in the hip of about fifty years old man is presented. The patient has a degenera• tive disease of the cord of syphilitic ethiology. This de• termined important therapeutic problems and had exceptional characteristics: great volume, rapid growth, calcifications and bone infiltration. Sorne considerations about ethiology, pathology, cli· nic and therapeutic of this agressive fibromatosis are done.